Almost multipliers and some of their properties - Ansari Piri, Esmaeil; Nouri, solmaz (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper we introduce the notion of almost multiplier maps and study some properties of these maps on a class of normed algebras, namely stable one. Also we compare the algebra of linear almost multipliers with the algebra of bounded linear operators.